The Effectiveness of Vocational High School Student Practicum Skills in Mixture Separation Materials on Problem-Solving Ability - Leny Heliawati; I.Ibnu Afakillah; I. Dwi Pursitasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study aims to analyze the effectiveness of chemistry practicum skills on students’ problem-solving abilities. The method used is descriptive research with a survey approach. The sample was determined using a simple random sampling probability technique, which included chemistry teachers from three different schools and 107 students from three schools. Indicators of practicum skills to problem-solving abilities ie students complete learning. Survey data were analyzed using quantitative descriptive techniques. The results showed that 74 people (69%) were in the good category and 33 people (39%) were in the very good category, and there were no students in the average, poor, and failed categories. So, it can be concluded that students' practicum skills on the separation of mixture material are effective in problem-solving skills.